Moderate Symptom-Based Exacerbations as Predictors of Severe Claims-Based Exacerbations in Asthma. (August 2013) - Lane, Sandi J.; Petersen, Hans; Seltzer, James M.; Blanchette, Christopher M.; Navaratnam, Prakash; Allen-Ramey, Felicia; Fuhlbrigge, Anne
Abstract : Objectives. Asthma exacerbations have well-established clinical and economic impact, yet lack consensus on characterization of an episode's severity. Asthma treatment guidelines outline the concept of a moderate asthma exacerbation; however, a clear definition that can be operationalized has not been proposed, Methods. Adult asthma (ICD-9: 493.XX) patients, with at least 9 months of continuous enrolment in the Fallon Community Health Plan were included in the retrospective cohort study. Patients diagnosed with Chronic Obstructive Pulmonary Disease (COPD) or other lower respiratory tract conditions were excluded. The first reported asthma-related event following a 2-week symptom-free period was designated as the index event. Asthma-related events were categorized as (1) moderate exacerbations (symptom-based) or (2) severe exacerbations (claims-based). Timing between and temporal sequence of asthma-related events along with average costs were calculated, Results. Of 3126 eligible patients, 55% reported an asthma-related event followed by a recurrent event(s). Moderate exacerbations followed by recurrent moderate exacerbations were most frequent (20%) with the shortest interval between exacerbations (mean: 83 days [SD 87]). Moderate exacerbations followed by severe exacerbations occurred in 16% of patients with an average of 176.74 (SD 176.94) days between events, Conclusions. Patient report of asthma bothersome enough to initiate contact with a clinician, but not requiring oral corticosteroid (OCS), is a definition for a moderate exacerbation that can be operationalized for research purposes. Further work is needed to demonstrate whether identification of moderate exacerbations will allow interventions that impact the frequency and timing of future exacerbations.